1999 Philippine statistical yearbook. (National Statistical Coordination Board, 1999)
Purpose: The book "presents in time series, statistics about the country's macro and micro environment and contain data which are disaggregated in different dimensions as useful tools in the conduct of feasibility studies, strategic planning and socio-economic policy decision making. For this issue, they included additional data on information technology and international statistics to enhance decision making and planning in government and in the private sector."